2006
DOI: 10.1177/147470490600400137
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Jealousy in Response to Actual Infidelity

Abstract: The present studies address two criticisms of the theory of evolved sex differences in jealousy: (a) that the sex difference in jealousy emerges only in response to hypothetical infidelity scenarios, and (b) that the sex difference emerges only using forced-choice measures. In two separate studies, one a paper-and-pencil survey with a student sample and the other a web-based survey targeting a non-student sample, men and women showed significant sex differences in jealousy in response to actual infidelity expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 15 publications
1
77
0
6
Order By: Relevance
“…Because "research that limits the definition of infidelity to sexual intercourse minimizes the devastating effects that other types of sexual involvement and emotional connections can have on relationships" (Blow & Hartnett, 2005, p. A plethora of researchers agree that both infidelity types must be explored in order to gain a more comprehensive understanding of this phenomenon, and many have done so in relation to which infidelity type is more distressing or upsetting: emotional infidelity or sexual infidelity. Across a multitude of studies, a reported sex difference has emerged regarding which infidelity type is viewed as more upsetting, with men seemingly more distressed by sexual infidelity as compared to women, and women experiencing more distress towards emotional infidelity than men (Buss, Larsen, Westen, & Semmelroth, 1992;Buss et al, 1999;Buunk, Angleitner, Oubaid, & Buss, 1996;Cramer, Abraham, Johnson, & Manning-Ryan, 2001;Cramer, Lipinski, Meteer, & Houska, 2008;DeSteno & Salovey, 1996;DeSteno, Bartlett, Braverman, & Salovey, 2002;Edlund, Heider, Scherer, Farc, & Sagarin, 2006;Fernandez, Vera-Villarroel, Sierra, & Zubeidat, 2007;Green & Sabini, 2004;Harris, 2003;Harris & Christenfeld, 1996;Penke & Asendorpf, 2008;Sabini & Green, 2004;Sagarin, Becker, Guadagno, Nicastle, & Millevoi, 2003;Schützwohl, 2008;Ward & Voracek, 2004).…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because "research that limits the definition of infidelity to sexual intercourse minimizes the devastating effects that other types of sexual involvement and emotional connections can have on relationships" (Blow & Hartnett, 2005, p. A plethora of researchers agree that both infidelity types must be explored in order to gain a more comprehensive understanding of this phenomenon, and many have done so in relation to which infidelity type is more distressing or upsetting: emotional infidelity or sexual infidelity. Across a multitude of studies, a reported sex difference has emerged regarding which infidelity type is viewed as more upsetting, with men seemingly more distressed by sexual infidelity as compared to women, and women experiencing more distress towards emotional infidelity than men (Buss, Larsen, Westen, & Semmelroth, 1992;Buss et al, 1999;Buunk, Angleitner, Oubaid, & Buss, 1996;Cramer, Abraham, Johnson, & Manning-Ryan, 2001;Cramer, Lipinski, Meteer, & Houska, 2008;DeSteno & Salovey, 1996;DeSteno, Bartlett, Braverman, & Salovey, 2002;Edlund, Heider, Scherer, Farc, & Sagarin, 2006;Fernandez, Vera-Villarroel, Sierra, & Zubeidat, 2007;Green & Sabini, 2004;Harris, 2003;Harris & Christenfeld, 1996;Penke & Asendorpf, 2008;Sabini & Green, 2004;Sagarin, Becker, Guadagno, Nicastle, & Millevoi, 2003;Schützwohl, 2008;Ward & Voracek, 2004).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Sex differences related to which infidelity type evokes more jealousy were examined by another group of authors using both forced-choice and continuous measures (Edlund et al, 2006).…”
Section: List Of Tablesmentioning
confidence: 99%
“…the second meta-analysis, presented by carpenter (2012) with 54 articles, states that data was not consistent with the evolutionary hypothesis, as the tendency of men to respond in this way was given only in samples of american students, whilst the other data supports the social-cognitive theory. However, the third meta-analysis -made by sagarin et al (2012) with 40 research papers on the subject -says that sex differences in jealousy is not a forced choice item; these emerge using continuous measurements and are not limited to responses to a hypothetical infidelity (Edlund, Heider, sherer, Farc, & sagarin, 2006).…”
Section: Personal Variablesmentioning
confidence: 99%
“…Non-evolutionary studies of jealousy have shown that factors such as relationship experience (Murphy et al 2006) experience with infidelity (Harris, 2002;Edlund, Heider, Scherer, Farc, & Sagarin, 2006;Johnson, 2006;Sagarin et al, 2012), and sexual orientation (Harris, 2002;DeSouza, Verderane, Taira, & Otta, 2006;Sagarin et al, 2003) are important moderators of how people perceive jealous threats. We also know from previous work that there is significant variation in the magnitude of the sex difference that is seen, as well as variation in how upset men and women are to different types of jealousy when it is measured continuously (Harris, 2003).…”
Section: Introductionmentioning
confidence: 99%